Capacity Building For The Clinical Investigation Of AIDS Malignancy In East Africa - Orem, Jackson; Otieno, Mwanda W.; Banura, Cecily; Mbidde, Edward Katongole; Johnson, John L.; Ayers, Leona; Ghannoum, Mahmoud; Fu, Pingfu; Feigal, Ellen G.; Black, Jodi; Whalen, Christopher; Lederman, Michael; et al. (Cancer Detection and Prevention, 2005)
To build capacity in the resource-poor setting to support the clinical investigation and treatment of AIDS-related malignancies in a region of the world hardest hit by the AIDS pandemic.An initial MEDLINE database search for international collaborative partnerships dedicated to AIDS malignancies in developing countries failed to identify any leads. This search prompted us to report progress on our collaboration in this aspect of the epidemic. Building on the formal Uganda-Case Western Reserve University (Case) Research Collaboration dating back to 1987, established NIH-supported centers of research excellence at Case, and expanding activities in Kenya, scientific and training initiatives, research capital amongst our institutions are emerging to sustain a international research enterprise focused on AIDS and other viral-related malignancies.A platform of clinical research trials with pragmatic design has been developed to further enhance clinical care and sustain training initiatives with partners in East Africa and the United States. An oral chemotherapy feasibility trial in AIDS lymphoma is near completion; a second lymphoma trial of byrostatin and vincristine is anticipated and a feasibility trial of indinavir for endemic Kaposi's sarcoma is planned.In the absence of published reports of evolving international partnerships dedicated to AIDS malignancy in resource constrained settings, we feel it important for such progress on similar or related international collaborative pursuits to be published. The success of this effort is realized by the long-term international commitment of the collaborating investigators and institutions to sustain this effort in keeping with ethical and NIH standards for the conduct of research; the provision of formal training of investigators and research personnel on clinical problems our East African partners are faced with in practice and the development of pragmatic clinical trials and therapeutic intervention to facilitate technology transfer and enhance clinical practice.
Keywords: AIDS malignancies; Capacity building; East Africa (Uganda; Kenya); Fogarty training; Clinical trials